Detrimental effects of physical inactivity on peripheral and brain vasculature in humans: Insights into mechanisms, long-term health consequences and protective strategies - Daniele, Alessio; Lucas, Samuel J. E.; Rendeiro, Catarina (Frontiers in Physiology, 2022)
The growing prevalence of physical inactivity in the population highlights the urgent need for a more comprehensive understanding of how sedentary behaviour affects health, the mechanisms involved and what strategies are effective in counteracting its negative effects. Physical inactivity is an independent risk factor for different pathologies including atherosclerosis, hypertension and cardiovascular disease. It is known to progressively lead to reduced life expectancy and quality of life, and it is the fourth leading risk factor for mortality worldwide. Recent evidence indicates that uninterrupted prolonged sitting and short-term inactivity periods impair endothelial function (measured by flow-mediated dilation) and induce arterial structural alterations, predominantly in the lower body vasculature. Similar effects may occur in the cerebral vasculature, with recent evidence showing impairments in cerebral blood flow following prolonged sitting. The precise molecular and physiological mechanisms underlying inactivity-induced vascular dysfunction in humans are yet to be fully established, although evidence to date indicates that it may involve modulation of shear stress, inflammatory and vascular biomarkers. Despite the steady increase in sedentarism in our societies, only a few intervention strategies have been investigated for their efficacy in counteracting the associated vascular impairments. The current review provides a comprehensive overview of the evidence linking acute and short-term physical inactivity to detrimental effects on peripheral, central and cerebral vascular health in humans. We further examine the underlying molecular and physiological mechanisms and attempt to link these to long-term consequences for cardiovascular health. Finally, we summarize and discuss the efficacy of lifestyle interventions in offsetting the negative consequences of physical inactivity.